A Study of Factors Associated with Consumer Snack Food Choices in Tastura Square, Praya City - Dyah Suryani; Widya Ariani (MEDICA (International Medical Scientific Journal), 2025)
Indonesian traditional food is highly diverse in terms of types, shapes, and colors. In the Tastura Square area, a wide variety of street food is available and widely consumed. Consumer behavior in choosing street food is generally influenced by affordable prices and good taste. This study aimed to determine the relationship between education level, knowledge, attitudes, age, gender, and social media with consumer behavior in selecting street food in the Tastura Square area, Praya City. A cross-sectional study design was used, involving 100 respondents selected through a simple random sampling technique. Data were collected using questionnaires and checklist sheets. Data analysis was conducted using univariate and bivariate methods, with the Chi-square test employed for statistical analysis. The results showed no significant relationship between education level (p = 1.000), attitude (p = 1.000), age (p = 1.000), and gender (p = 1.000) with consumer behavior. However, a significant relationship was found between knowledge (p = 0.006) and social media (p = 0.002) with consumer behavior in choosing street food. Therefore, it is recommended that viral content promoting healthy food choices be intensified on social media to raise awareness among consumers when selecting street snacks.